Antivenom Effects of 1, 2, 3-Triazoles against Bothrops jararaca and Lachesis muta Snakes. (22nd April 2013) - Domingos, Thaisa F. S.; Moura, Laura de A.; Carvalho, Carla; Campos, Vinícius R.; Jordão, Alessandro K.; Cunha, Anna C.; Ferreira, Vitor F.; de Souza, Maria Cecília B. V.; Sanchez, Eladio F.; Fuly, André L.
Abstract : Snake venoms are complex mixtures of proteins of both enzymes and nonenzymes, which are responsible for producing several biological effects. Human envenomation by snake bites particularly those of the viperid family induces a complex pathophysiological picture characterized by spectacular changes in hemostasis and frequently hemorrhage is also seen. The present work reports the ability of six of a series of 1, 2, 3-triazole derivatives to inhibit some pharmacological effects caused by the venoms of Bothrops jararaca and Lachesis muta . In vitro assays showed that these compounds were impaired in a concentration-dependent manner, the fibrinogen or plasma clotting, hemolysis, and proteolysis produced by both venoms. Moreover, these compounds inhibited biological effects in vivo as well. Mice treated with these compounds were fully protected from hemorrhagic lesions caused by such venoms. But, only the B. jararaca edema-inducing activity was neutralized by the triazoles. So the inhibitory effect of triazoles derivatives against some in vitro and in vivo biological assays of snake venoms points to promising aspects that may indicate them as molecular models to improve the production of effective antivenom or to complement antivenom neutralization, especially the local pathological effects, which are partially neutralized by antivenoms.